2006
DOI: 10.1016/j.immuni.2006.06.020
|View full text |Cite
|
Sign up to set email alerts
|

NTB-A Receptor Crystal Structure: Insights into Homophilic Interactions in the Signaling Lymphocytic Activation Molecule Receptor Family

Abstract: The signaling lymphocytic activation molecule (SLAM) family includes homophilic and heterophilic receptors that regulate both innate and adaptive immunity. The ectodomains of most SLAM family members are composed of an N-terminal IgV domain and a C-terminal IgC2 domain. NK-T-B-antigen (NTB-A) is a homophilic receptor that stimulates cytotoxicity in natural killer (NK) cells, regulates bactericidal activities in neutrophils, and potentiates T helper 2 (Th2) responses. The 3.0 A crystal structure of the complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
55
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 54 publications
4
55
0
Order By: Relevance
“…7). The CD84 head-to-tail dimer exhibited the same twofold symmetrical organization recently reported for the full NTB-A ectodomain and, most important, is consistent with the formation of an intercellular (T cell-APC) homophilic dimer that can support signaling (see below) (12).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…7). The CD84 head-to-tail dimer exhibited the same twofold symmetrical organization recently reported for the full NTB-A ectodomain and, most important, is consistent with the formation of an intercellular (T cell-APC) homophilic dimer that can support signaling (see below) (12).…”
Section: Discussionsupporting
confidence: 81%
“…In combination with previously published work (12,13), the current study demonstrated that the homophilic affinities span at least three orders of magnitude. This finding suggested that differences in affinities might be a contributor to the different signaling behavior exhibited by the individual family members.…”
supporting
confidence: 87%
See 2 more Smart Citations
“…NTB-A molecules, the human Ly108 homolog, form homodimers in solution with an equilibrium dissociation constant of ∼2 mM (14). Whereas this modest affinity would not allow Ly108 to mediate cell-cell adhesion, prolonged membrane juxtaposition in the absence of TCR or SAP-dependent signal transduction can drive Ly108 into the interface of cell couples, likely because of the reduced diffusibility after trans engagement.…”
Section: Discussionmentioning
confidence: 99%